2016
DOI: 10.1111/fog.12147
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic fluctuations of blue whiting (Micromesistius poutassou) linked to open‐sea convection processes in the northwestern Mediterranean

Abstract: In the Mediterranean, blue whiting, Micromesistius poutassou, constitutes a traditional fisheries resource. Over several decades, blue whiting landings in the Catalan coast (northwestern Mediterranean) have displayed cyclical variations, of c. 6 yrs, slightly decreased to five in the last two decades, as shown through wavelet analysis. These fluctuations have persisted under very different levels of fishing effort. This study evaluates the hypothesis that deep-water formation in the adjacent Gulf of Lions, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 59 publications
0
21
1
Order By: Relevance
“…In the most recent years, the total catch of blue whiting in the study area remained at very low levels. Since 2012 landings remained at ≤ 500 t (Generalitat de Catalunya, 2019) lower than the minimum values reported by Martin et al (2016Martin et al ( ) over a period 1961Martin et al ( -2011 suggests that the stock would not show sign of recovery. The length of blue whiting individuals captured by bottom trawl ranged between 3 and 39 cm TL, and differences related with sex were found, with females reaching larger sizes than males.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In the most recent years, the total catch of blue whiting in the study area remained at very low levels. Since 2012 landings remained at ≤ 500 t (Generalitat de Catalunya, 2019) lower than the minimum values reported by Martin et al (2016Martin et al ( ) over a period 1961Martin et al ( -2011 suggests that the stock would not show sign of recovery. The length of blue whiting individuals captured by bottom trawl ranged between 3 and 39 cm TL, and differences related with sex were found, with females reaching larger sizes than males.…”
Section: Discussionmentioning
confidence: 75%
“…Blue whiting, Micromesistius poutassou (Risso, 1827), is a pelagic gadoid widely distributed in the North Atlantic and the Mediterranean Sea, inhabiting over the shelf edge and continental slope (Bailey, 1982;Heino et al, 2008). There is large amount of information on its biology, behavior and fisheries for the Northeast Atlantic (Bailey and Heath, 2001;Bailey, 1982;Gonçalves et al, 2017;Hátún et al, 2009;Payne et al, 2012), but less is known for the species in the Mediterranean despite it has an important commercial interest, particularly in the northern part (Bas, 1963;Bas and Calderon-Aguilera, 1989;Martin et al, 2016;Orsi-Relini and Peirano 1985;Serrat et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, during the past two decades, landings of M. poutassou in the Mediterranean Sea have fallen from almost 30,000 t to just 2000 t in 2016 (GFCM, ). It has been shown that variation in M. poutassou population parameters is linked to fluctuations in environmental and hydrodynamic factors (Martin et al, ; Trenkel et al, ) as well as overfishing (Bas & Calderon‐Aguilera, ; Rueda et al, ). For these reasons, we need to assess the life‐history traits and the trade‐offs among them, for species such as these inhabiting the Mediterranean Sea.…”
Section: Introductionmentioning
confidence: 99%
“…The winter-spring bloom is the main contributor to the overall phytoplankton biomass and primary production in the northwestern basin (Bosc et al, 2004;Estrada et al, 2014) and fuels energy to micro and mesozooplankton that support key ecosystem components, from pelagic fish (e.g., Martin et al, 2016) to marine birds (Ramírez et al, 2016). Fluctuations in the intensity of vertical mixing result in interannual variations in the extent of the winter-spring phytoplankton bloom and zooplanktonic biomass (Vandromme et al, 2011;Severin et al, 2014) and have been related with the recruitment success of pelagic species that reproduce in winter, such as blue whiting, Micromesistius poutassou, and sardine, Sardina pilchardus (Lloret et al, 2004;Martin et al, 2016). Section "Interannual Variability" discusses the range of interannual variability represented by the models.…”
Section: Winter Mixing and Phytoplankton Bloommentioning
confidence: 99%